PROFIL KONTROL DIRI PESERTA DIDIK DALAM BELAJAR DI KELAS XI SMA NEGERI 1 RAMBATAN KABUPATEN TANAH DATAR - Linda, Resci Nova; Kasih, Fitria; Wira Nita, Rahma (Bimbingan dan Konseling, 2013)
Based on the observation found that researchers do learners have self-control in a different study, the researchers raised concerns about the research: how the profile of self-control learners studying in Class XI in SMAN 1 Rambatan Kabupaten Tanah Datar. This study aims to reveal: 1) Self-control students in learning viewed from the aspect of Â behavioral control, 2) Self-control students in learning from the aspects of cognitive control, 3) Self-control students in learning viewed from the aspect of decessional control). This research is a descriptive study sought to describe a situation for what it is. The population in this study were all students of class XI with the number 217. Techniques used in sampling is simple random sampling. So the sample size of 68 people. The instrument used in this study was a questionnaire. While the data used for the analysis of the percentage formula. The research results revealed that: 1) Self-control students in learning viewed from the aspect of Â behavioral control on both criteria. 2) Self-control students in learning from the aspects of cognitive control on both criteria. 3) Self-control students in learning viewed from the aspect of decessional control Â on both criteria.